Effects of High-Glucose Environment on Periodontal Ligament Cell Proliferation and Apoptosis via NF-κB Signaling Pathway: High-Glucose Effects on Periodontal Ligament Cell - Wu, Libo; Huang, Gan; Liu, Longkun; Zhang, Qin; Hu, Jie; Pan, Shuting (Cellular and Molecular Biology, 2022)
The purpose of this study was to discuss the function of the high-glucose environment on the periodontal ligament cell (PDLC) proliferation and apoptosis and the action mechanism of the NF-κB signaling pathway in this process. For this purpose, the human PDLCs were cultured in vitro using 5.5 mM (control group)/24.0 mM glucose (HG group) of glucose and 10 μM of QNZ+24.0 mM of glucose (HG+QNZ), respectively, and the cell proliferation level was checked through CCK-8 assay. TUNEL assay was used to perform cell apoptosis. ELISA was utilized to explore the secretion levels of the proinflammatory factors interleukin (IL)-1β and IL-6 proteins. The p65 and p50 proteins level were tested via the Western blotting (WB) assay. Results showed that in comparison with the control group, 24.0 mM of glucose could significantly decrease the proliferation ability of the PDLCs (p<0.01), cause cell apoptosis (p<0.05) and promote the secretion of IL-6 and IL-1β (p<0.05). The expressions of p65 and p50 proteins were up-regulated obviously in the high-glucose environment (p<0.05). QNZ could exert a specific inhibitory effect on the NF-κB activity to significantly down-regulate the expressions of p65 and p50 proteins (p<0.05) and reverse the effects of the high-glucose environment on the cell apoptosis and proliferation (p<0.05). In conclusion, hyper-glucose may affect PDLC proliferation and apoptosis by suppressing the NF-κB signaling pathway activity.